2006
DOI: 10.1021/la060928q
|View full text |Cite
|
Sign up to set email alerts
|

Bridge-Bonded Formate:  Active Intermediate or Spectator Species in Formic Acid Oxidation on a Pt Film Electrode?

Abstract: We present and discuss the results of an in situ IR study on the mechanism and kinetics of formic acid oxidation on a Pt film/Si electrode, performed in an attenuated total reflection (ATR) flow cell configuration under controlled mass transport conditions, which specifically aimed at elucidating the role of the adsorbed bridge-bonded formates in this reaction. Potentiodynamic measurements show a complex interplay between formation and desorption/oxidation of COad and formate species and the total Faradaic cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
295
1
12

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(332 citation statements)
references
References 38 publications
21
295
1
12
Order By: Relevance
“…Very importantly, they reported that CO ad acts not only as a poison or site-blocking species but it also inhibits the formate decomposition step. However, using a similar experimental approach, Behm and co-workers 52 have recently demonstrated that adsorbed bridge-bonded formate species cannot be considered as a reaction intermediate in the main reaction pathway during formic acid electrooxidation on platinum. The authors proposed a triple pathway mechanism including the direct pathway, the indirect pathway, and the formate pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Very importantly, they reported that CO ad acts not only as a poison or site-blocking species but it also inhibits the formate decomposition step. However, using a similar experimental approach, Behm and co-workers 52 have recently demonstrated that adsorbed bridge-bonded formate species cannot be considered as a reaction intermediate in the main reaction pathway during formic acid electrooxidation on platinum. The authors proposed a triple pathway mechanism including the direct pathway, the indirect pathway, and the formate pathway.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13] Electrocatalytic reactions rates depend on the surface structure of the electrodes. So, Pt(111) electrodes exhibit low activity through the active intermediate and negligible CO formation, whereas Pt(100) surfaces show the highest activity for both routes.…”
Section: Introductionmentioning
confidence: 99%
“…20 It has been pointed out that, in the oxidation process of formic acid on pure platinum electrodes, adsorbed formate plays an important role. This specie has been detected by FTIR [9][10][11][12][13] and voltammetry, 21 coinciding the onset for the oxidation process with that for the adsorption of formate. 21 Also, DFT calculations indicate that adsorbed formate is a key element in the considered oxidation process.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the reaction route which gives directly CO 2 is called the direct oxidation route. For this route, the nature of the intermediate is still subject of discussion [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%